Analisis Ketimpangan Sosial di Tengah Pertumbuhan Ekonomi dalam Perspektif Ekonomi Islam - Alfin Miftahul Akmal; Cintia Putri Peayogha; Fernanda Septianayla Putri; Tanadda Shidqi (Indo Publishing, 2026)
Economic growth is widely recognized as a fundamental indicator for assessing the success of a country's development process. Nevertheless, an increase in economic growth does not necessarily guarantee an equitable distribution of welfare across society. This situation may give rise to social inequality, which is reflected in disparities in income levels, access to education, healthcare services, and economic opportunities among different social groups. This study aims to examine social inequality in the context of economic growth and to analyze the issue from the perspective of Islamic economics. The discussion is grounded in theories of economic growth, social inequality, and wealth distribution within the framework of Islamic economics. This research adopts a qualitative approach through a literature review methodology. The data were collected from various secondary sources, including scientific journals, academic books, scholarly articles, and other relevant documents. The findings reveal that economic growth alone is insufficient to reduce social inequality unless it is accompanied by a fair and balanced distribution of welfare. From the standpoint of Islamic economics, social inequality can be alleviated through the application of distributive justice principles and the effective utilization of Islamic economic instruments, such as zakat, infaq, sadaqah, and waqf. Therefore, Islamic economics provides a comprehensive framework for promoting equitable, inclusive, and sustainable economic growth.